Improving the interaction of Down syndrome students through the use of RFID technology - Jadán-Guerrero, Janio (2016)
Interactive systems aimed at educational environments are becoming increasingly important in students learning. This paper focuses on the application of Radio Frequency (RFID) technology in early literacy process of Down syndrome students. An experimental study was carried out in Costa Rica among four special education teachers and six Down syndrome students of a Special Education School. The research aimed to measure the interaction between participants and three user interfaces: traditional interface based on cardboard cards, Graphic User Interface (GUI) based on digital cards and Tangible User Interface (TUI) based on 3D letters and low cost toys with RFID tags. The method consisted of the registration of occurrences in the behavior of participants. The results obtained from the application of the Friedman test confirmed the exploratory findings carried out in a qualitative previous work, in which TUI improves the interaction in early literacy process of Down syndrome students. © 2016 IEEE.